The complexity of the differential diagnosis of heart tumors and pericarditis - R.M. Vitovskyi; V.V. Isaienko; E.V. Aksyonov; I.G. Yakovenko; M.A. Tregubova; O.A. Mazur (Кардіохірургія та інтервенційна кардіологія)
The article describes an unusual course and complex differential diagnosis of fibrotic pericarditis, which imitated a heart tumor at the base of aorta. The key point in the progression of the disease was the appearance of concomitant fungal infection, which led to the emergence of its clinical manifestations. Due to the external compression of the main trunk of the left coronary artery up to 90 %, its stenting was performed. A biopsy followed by histopathological examination, along with other diagnostic methods, allowed to prescribe an adequate treatment for this pathology